Using Picture Media in Improving Students Learning Outcomes on The Lesson of Muthala'ah - Hafidz, Abdul; Hasanah, Maghfirotul; Mahmudi, Ihwan; Safii, Aufal Muhammad; Wahid, Abdul (Arabi : Journal of Arabic Studies, 2023)
Picture is one of media that can be used in learning Muthala'ah lesson to make it easier for teachers and students to understand the lesson and improve learning outcomes. This research uses one-group design through a pre-test and post-test. All students of class III Intensive D TMI (female) with a total of 23 students were used as the research population, and what will be used as a research sample is the total number of students or 100% of the total population. Based on the analysis carried out in this study, using pictures influences student learning outcomes. The result of student pre-test of 5.84 before using picture media and the results of the student post-test after using the picture media are 7.19. Based on these results, it can be stated that the value of students in class III Intensive D TMI (female) increased by 20% in learning Muthala'ah lesson after using Picture media, and it can be concluded that picture media is effectively used in teaching and learning activities of Arabic language, especially on Muthala'ah lesson.